2009
DOI: 10.1098/rsbl.2009.0032
|View full text |Cite
|
Sign up to set email alerts
|

Stress and the costs of extra-territorial movement in a social carnivore

Abstract: Costs associated with extra-territorial movement are believed to have favoured the evolution of delayed dispersal and sociality across a range of social vertebrates, but remain surprisingly poorly understood. Here we reveal a novel mechanism that may contribute substantially to the costs of extra-territorial movement: physiological stress. We show that subordinate male meerkats, Suricata suricatta , exhibit markedly elevated faecal glucocorticoid metabolite levels (a non-invasive measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
81
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 10 publications
1
81
0
2
Order By: Relevance
“…There have been only a few such studies conducted in free-ranging carnivores. One example is the work of Young and Monfort [61] who have demonstrated that prolonged extraterritorial movement in subordinate meerkats (Suricata suricatta) markedly elevates glucocorticoid metabolites that, in turn, compromises fitness and health. An investigation of African wild dogs (Lycaon pictus) that were captured from nature and held in enclosures for 22 weeks has revealed an abrupt rise in excreted glucocorticoids followed by a decline of hormone concentration to baseline level within 2 weeks of being in captivity [11].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…There have been only a few such studies conducted in free-ranging carnivores. One example is the work of Young and Monfort [61] who have demonstrated that prolonged extraterritorial movement in subordinate meerkats (Suricata suricatta) markedly elevates glucocorticoid metabolites that, in turn, compromises fitness and health. An investigation of African wild dogs (Lycaon pictus) that were captured from nature and held in enclosures for 22 weeks has revealed an abrupt rise in excreted glucocorticoids followed by a decline of hormone concentration to baseline level within 2 weeks of being in captivity [11].…”
Section: Introductionmentioning
confidence: 97%
“…This presents distinct advantages (over urine) for case of collecting specimens. Specifically and depending on species specificities, fecal corticoid concentrations and patterns have reflected changes or differences in carnivore social status (African wild dog [12], gray wolves [Canis lupus, [50]], spotted hyena [Crocuta crocuta, [18], meerkat [61]), acclimation to new territory post-translocation (African wild dog [11]) and reaction to increased human activities in native habitat (gray wolf [13], spotted hyena [58]). …”
Section: Introductionmentioning
confidence: 99%
“…Immunoassays originally designed to target native (i.e., nonmetabolized) glucocorticoids have been extensively used to quantify fecal glucocorticoid metabolites in an array of species (Harper and Austad 2000;Wasser et al 2000;Young and Monfort 2009). These assays assume that the antibody has sufficient cross-reactivity to recognize (a group of) metabolites of the parent hormone and that an increase in blood glucocorticoid secretion leads to an increase in metabolite excretion in the feces.…”
Section: Introductionmentioning
confidence: 99%
“…Although these assays have different cross-reactivities and hence different efficacy, they have been used with success to study relationships between fecal glucocorticoid metabolite levels and some aspects of the reproduction or the ecology of the animals in their natural environment (Jurke et al 1997;Lynch et al 2002;Mateo 2007;Young and Monfort 2009). Other studies use antibodies designed to recognize a group of fecal glucocorticoid metabolites sharing a common structure (Jurke et al 1997;Lynch et al 2002;Möstl and Palme 2002;Möstl et al 2005;Mateo 2007;Young and Monfort 2009). These metabolite antibodies typically yield higher concentrations of measured metabolites and display a higher reactivity with the fecal glucocorticoid metabolites than antibodies targeting native glucocorticoids and are therefore more likely to detect small fluctuations in fecal glucocorticoid metabolites (Morrow et al 2002;Frigerio et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…; Thorn et al . ), and be used to develop basic ethograms of animal behaviours (Young & Monfort ). These non‐invasive survey techniques, such as photographic surveys, and survey designs such as distance sampling have also enabled scientists to quantify both mortality and recruitment rates in wildlife populations, even for rare and elusive species (Marucco et al .…”
Section: Introductionmentioning
confidence: 99%